2017
DOI: 10.7251/jtttp1701028p
|View full text |Cite
|
Sign up to set email alerts
|

Analisys of the influence of alcohol on the motor skills and attention of a driver

Abstract: Alcohol is recognized as one of the factors in the occurrence of traffi c accidents, which signifi cantly aff ects the occurrence of accidents and the severity of their consequences. In this paper, the results of the pilot survey present the measures of infl uence of intoxicated drivers on the status of their motor skills and a en on in traffi c. The eff ect of alcohol is simulated using the "drunk glasses" that simulate the eff ects of the alcohol on the human body: reduced alertness, slowed reac ons, confusi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 2 publications
0
1
0
Order By: Relevance
“…For example, a study examined 1,397 patients treated for motor vehicle injuries and found that alcohol-related impairment was strongly related to greater injury in non-admitted patients, even when crash severity was taken into account (Waller et al, 1989). In basic studies, it has been widely demonstrated that eye movements (Watten and Lie, 1997;Harvey, 2014;Tyson et al, 2021), basic perception (Wang et al, 2021), cognition (Silva et al, 2017;Zhang et al, 2020), emotion (Eastwood et al, 2020), and motor skills (Brumback et al, 2007;Petrović et al, 2017) are disrupted by alcohol intake and that the extent of these disruptions depends on the dose of alcohol. Negative effects have been observed even when subjects have low-to-moderate blood alcohol concentration (BAC) (Eckardt et al, 1998;Abroms et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…For example, a study examined 1,397 patients treated for motor vehicle injuries and found that alcohol-related impairment was strongly related to greater injury in non-admitted patients, even when crash severity was taken into account (Waller et al, 1989). In basic studies, it has been widely demonstrated that eye movements (Watten and Lie, 1997;Harvey, 2014;Tyson et al, 2021), basic perception (Wang et al, 2021), cognition (Silva et al, 2017;Zhang et al, 2020), emotion (Eastwood et al, 2020), and motor skills (Brumback et al, 2007;Petrović et al, 2017) are disrupted by alcohol intake and that the extent of these disruptions depends on the dose of alcohol. Negative effects have been observed even when subjects have low-to-moderate blood alcohol concentration (BAC) (Eckardt et al, 1998;Abroms et al, 2015).…”
Section: Introductionmentioning
confidence: 99%